Impact of dialysis modality choice on the survival of end-stage renal disease patients with congestive heart failure in southern China: A retrospective cohort study - He, Zhiren; Liang, Hui; Huang, Jing; Zhang, Defei; Ma, Hongyan; Lin, Junjie; Cai, Youqing; Liu, Tonghuan; Li, Hucai; Qiu, Weizhong; Wang, Lingzheng; Yuan, Fengling; et al. (Frontiers in Medicine, 2022)
Background and object Heart failure is one of the common complications in patients with end-stage renal disease (ESRD) and a major cause of death in these patients. The choice of dialysis modality for ESRD patients with congestive heart failure (CHF) is still inconclusive. The purpose of this study was to compare the prognosis of hemodialysis (HD) and peritoneal dialysis (PD) among ESRD patients with CHF and provide a basis for clinical decision-making. Materials and methods This was a retrospective study conducted at Guangdong Provincial Hospital of Traditional Chinese Medicine that included patients with CHF requiring long-term renal replacement therapy between January 1, 2012 and December 31, 2017. The end of follow-up was December 31, 2020. All patients were divided into HD and PD groups and sub grouped by age, and we used univariate and multifactorial Cox regression analyses to calculate the relative hazard ratios (HR) of the different dialysis types and adjusted for differences in baseline data using propensity score matching (PSM). Result A total of 121 patients with PD and 156 patients with HD were included in this study. Among younger ESRD patients (≤65 years of age) with CHF, the prognosis of HD was worse than that of PD [HR = 1.84, 95% confidence interval (CI) = 1.01–3.34], and this disadvantage remained significant in the fully adjusted model [sex, age at dialysis initiation, Charlson comorbidities index, body mass index, prealbumin, hemoglobin, and left ventricular ejection fraction (LVEF)] and after PSM. In the older group (>65 years of age), the prognosis of HD was better than that of PD (HR = 0.46, 95% CI = 0.25–0.85), and the protective effect remained in the fully adjusted model and after PSM. The aforementioned survival differences across the cohort were maintained in patients with preserved LVEF (>55%), but could not be reproduced in patients with reduced LVEF (≤55%). Conclusion In southern China, PD is a better choice for younger patients with ESRD, CHF and preserved LVEF, and HD is the better option for older patients.